Growth Performance of Clarias gariepinus in Paddy Rice Field in Kwadon, Gombe, Nigeria (Asian Journal of Plant Biology, 2023)
In this scenario, a rice and fish farming system is merged, where the fish are farmed alongside or interchangeably with the rice. Integrated fish farming is a sequential linkage between two or more farming operations. However, occasionally the advancement of rice-fish farming has been ham-pered by changes in rice growing methods as well as the widespread use of insecticides and artifi-cial fertilizers. A cutting-edge agricultural technique where the primary crop is rice and fish fin-gerlings are used as a secondary source of income. By generating employment opportunities and ensuring food security, rice cum fish culture not only helps farmers who are living in poverty to earn more money but also increases the output of their paddy crops.  This study aims to assess the performance of the fish as a result of the rice-fish culture. Kwadom, in the Yamaltu-Deba local government area of Gombe State, Nigeria, practiced rice-fish culture. The study used six (6) rice paddy fields with the labels "pond X and X1 received artificial feed, pond Y and Y1 received poultry dropping, and pond Z and Z1 serve as control." at twenty-one (21) days following plant-ing, local rice seedlings Jamila and improved rice seedlings Faro 44 were transferred into the paddies. Each pond received 5 g of Clarias gariepinus per fingerling. But only one treatment (X and X1) produced positive results for the rice variety faro 44, which managed to live.  When compared to the other 2 treatments (poultry dropping and control), the fish output in treatment one (artificial feed) had an overall weight (g) of 54000 g, which is considerably greater. The study's high mean in faro 44 reading of 96264.73 g was observed. An analysis of resource use efficiency found that, with the exception of labour, irrigation, and insecticide, most resources in the rice-fish industry were underutilized by farmers. In order to improve food security and maintain sustained rural development, it is crucial that the government actively supports the integration of rice and fish farming.
Keywords: Rice and fish culture; Clarias gariepinus; Faro 44; Jamila; Nigeria